Content Analysis of Medicinal Plants theses of Pharmaceutical Faculties between 1998-2006 and Publishing Rate of their Results in the Scientific Journal Articles - M Shekofteh; F Akbari (Institue of Medicinal Plants, ACECR, 2009)
Background: Pharmaceutical theses including medicinal plants subjects are invaluable informative sources. If they are disseminated properly, many research problems can be solved. Unfortunately, theses results are almost ignored. Content analysis is a bibliometrics technique that is applied in many subjects to help us know what the researchers have done before. Another way of information dissemination about the results of theses is through publishing in the scientific research journals. In this article, the medicinal plants theses conducted in the years between 1998 and 2006 have been analyzed and searched in the SID database to determine the number of theses that have been published as articles in scientific journals. Methods: The Technique used in this descriptive research is content analysis. This survey aims at specifying medicinal plants, according to their family, genus and species in the medicinal plants theses and their subject. Besides, the SID database was searched to determine the number of theses that their results have been published as journal articles. Results: The results indicated that medicinal plants theses comprised %20 of total theses. The family of "Labiatae" including 24 genus and 36 species and the genus "Tanacetum" including 13 species showed the great variation. Most of theses were about the specieses "danae racemosa" & "zataria multiflora". The Main subjects of dissertations were "phytochemistry", "pharmacological effects" and "essential oils". Only %7.4 of theses was published as articles in the scientific journals. Conclusion: publishing of the result of theses as scientific articles plays very significant role in pharmaceutical information dissemination. The Pharmacy faculties should be aware of the past researches to orient the students to choose the appropriate theseschr('39') subjects. Making data bases could be useful in this regard.